Matters of concerns and user stories: ontological and methodological considerations for collaborative design processes. Issue 3 (2nd July 2020) - Poderi, Giacomo; Hasselqvist, Hanna; Capaccioli, Andrea; Bogdan, Cristian; D'Andrea, Vincenzo
ABSTRACT: In this article, we lever on matters of concern (MoC) as a way to reflect on the articulation of collaborative design processes. We do this by focusing on an international project for the development of an ICT platform for energy management at the household and housing cooperative levels. We analyse retrospectively how the project development process captured and accompanied several MoC in two piloting areas, where all authors were directly involved. Our work contributes to the body of knowledge that builds on Science and Technology Studies scholarship to enrich the understanding of complex design processes. In particular, the paper goes beyond a descriptive take on MoC and provides ontological and methodological considerations on the use of user stories. Ultimately, the paper argues that scaffolding tools, such as user stories, can capture and convey MoC, and they can facilitate a transparent process of actor-networks alignment and emergence.